Über Projektionen: Weltkarten und Weltanschauungen Von der Rekonstruktion zur Dekonstruktion, von der Konvention zur Alternative - Stirnemann, Julia Mia (Image, 2018)
"About projections" gives insights into world maps, their ways of representation and the associated worldviews. On the one hand, the projection is presented as an ideal projection in the sense of a worldview that describes prevailing mental images, values, order principles, ways of thinking or explanatory models of the world. On the other hand, the focus is on the geometric projection that underlies world maps: every world map faces the difficulty of displaying the spherical surface in a two-dimensional plane. In a reconstruction various paradigmatic worldviews are shown on the basis of world maps. In a deconstruction, conventional ones are contrasted by alternative world maps. The wide variety of possible world maps shows that world maps do not represent a status quo, but are merely a subjective interpretation of the world at a given time, which remain subject to constant upheavals.